The role of modern communication technology in improving the decision-making process from the point of view of the staff of the Directorate of Youth and Sports of the province of Khenchela - layadi abdelhakim; rabah.berbakh; asaiadi marouan (sports creativity, 2025)
Our study aimed to find out the correlation between communication technology and decision-making process from the point of view of the staff of the Directorate of Youth and Sports of the province of Khenchela, our study consisted of 30 employees, were selected in a comprehensive survey method, and we used the descriptive method, and our research tool was a questionnaire. Some of the most important results are: - A strong correlation between the communication technologies used and the decision-making process of the staff of the Directorate of Youth and Sports of Khenchela.